2012
DOI: 10.1200/jco.2011.40.1836
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Versus Postoperative Chemoradiotherapy for Locally Advanced Rectal Cancer: Results of the German CAO/ARO/AIO-94 Randomized Phase III Trial After a Median Follow-Up of 11 Years

Abstract: There is a persisting significant improvement of pre- versus postoperative CRT on local control; however, there was no effect on overall survival. Integrating more effective systemic treatment into the multimodal therapy has been adopted in the CAO/ARO/AIO-04 trial to possibly reduce distant metastases and improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
1,100
3
38

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,764 publications
(1,237 citation statements)
references
References 14 publications
42
1,100
3
38
Order By: Relevance
“…For these patients, neoadjuvant chemoradiotherapy followed by total mesorectal excision (TME) is the standard regimen [2] [3]. It has been reported that preoperative neoadjuvant chemoradiotherapy not only decreases the local recurrent probability, but also increases the anus preservation rate when compared to postoperative chemoradiotherapy [4].…”
Section: Introductionmentioning
confidence: 99%
“…For these patients, neoadjuvant chemoradiotherapy followed by total mesorectal excision (TME) is the standard regimen [2] [3]. It has been reported that preoperative neoadjuvant chemoradiotherapy not only decreases the local recurrent probability, but also increases the anus preservation rate when compared to postoperative chemoradiotherapy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Perez et al 133 have reported a 15% LR rate after LE at 15 months in 27 patients with clinical stage II or III disease who experienced a partial clinical response after CRT. Because the median time to LR in patients with LARC treated by TME after CRT is 3 years, and because almost one third of recurrences are diagnosed after 5 years, 134 it can be expected that the recurrence rate will continue to increase as follow-up matures. In addition, recent work by Park et al 48 noted that patients with an intermediate (ypT1-2N0) or poor (ypT3-4 or Nϩ) response experienced significantly worse 5-year PFS, LR, and distant recurrence compared with patients with a pCR, suggesting more aggressive biologic behavior.…”
mentioning
confidence: 99%
“…The benefit of radiotherapy is not limited in long-term local control of the disease, as was shown in an update of the German Trial after 11 years of follow-up [20]. One of the main consequences is its capability to lead to tumor regression on different levels: the size of primary tumor (downsizing) and the depth of wall and nodes infiltration (downstaging).…”
Section: Discussionmentioning
confidence: 99%